Studi Etnofarmasi dan Identifikasi Faktor-Faktor yang Mempengaruhi Penggunaan Tumbuhan Obat sebagai Terapi Hipertensi pada Masyarakat Desa Poka, Kecamatan Teluk Ambon, Kota Ambon, Provinsi Maluku: Ethnopharmacy Study and Identification Of Factors Affecting The Use Of Medicinal Plants As Hypertension Therapy in The Community Of Poka Village, Teluk Ambon District, Ambon City, Maluku Province - Carlos Fransisco Rumangun; Agus Kurniawan (Universitas Gunadarma, 2025)
Ethnopharmacy is an approach used to explore the traditional use of medicinal plants within communities, which holds potential for the development of modern medicines. Hypertension is one of the non-communicable diseases that continues to pose a global health threat and requires proper management. This study aims to identify the types of plants used by the community for hypertension therapy, their processing methods, and the factors influencing their use. The method applied was observational with a cross-sectional design, conducted through questionnaires and interviews. Plant samples mentioned by the community were collected as herbarium specimens and analyzed for their chemical compound groups. The research conducted in Poka Village revealed 10 types of plants used for managing hypertension, including cat’s whiskers, Phyllanthus niruri, moringa, African leaf, basil, celery, lemongrass, pandan, soursop, and gotu kola. The three most commonly used plants were cat’s whiskers (17.5%), Phyllanthus niruri (15%), and moringa (15%). Information regarding their use was primarily obtained from family traditions (40%). Usage was irregular and typically applied only when necessary, with the most common preparation method being boiling (51%). The main factors influencing the use of herbal therapy included: natural ingredients (22.5%), easy availability (20%), family traditions (15%), fewer side effects (12.5%), and beliefs in their effectiveness and affordability. These findings highlight the need for government-led education and outreach to ensure the safe and optimal use of herbal medicine.